Excessive numbers of skin cancers and pre-malignant skin lesions in an Australian heart transplant recipient. - Bouwes Bavinck, J. N. (1995)
One and a half years after heart transplantation an Australian man developed his first skin cancer. In the period until his death, 7 years after the transplantation, 34 histologically confirmed squamous cell carcinomas developed, 17 intra-epidermal carcinomas, and 9 basal cell carcinomas. Most skin cancers were confined to chronically sun exposed sites. Exposure to sunlight and human papillomavirus are important factors in the development of skin cancer in renal transplant recipients, and further studies are needed to establish the role of these risk factors in cardiac transplant recipients.